Analysis, Architectures and Modelling of Embedded Systems Third IFIP TC 10 International Embedded Systems Symposium, IESS 2009, Langenargen, Germany, September 14-16, 2009, Proceedings - Rettberg, Achim; Zanella, Mauro C.; Amann, Michael; Keckeisen, Michael; Rammig, Franz J. (IFIP Advances in Information and Communication Technology, 2009)
This book constitutes the refereed proceedings of the third IFIP TC 10 International Embedded Systems Symposium, IESS 2009, held in Langenargen, Germany, in September 2009. The 28 revised papers were selected from 46 submissions. The papers are organized in topical sections on modelling; transaction level modelling; scheduling and real-time systems; simulation, verification and test; platforms and processors; automotive systems; and wireless sensor networks. The volume also includes three case studies and two tutorials.